Chemoembolization as a minimally invasive treatment of primary malignant liver cancer - Katarzyna Szklener; Weronika Kuryło; Anna Rodzajewska; Łukasz Światłowski; Tomasz Jargiełło; Sławomir Mańdziuk (Kazimierz Wielki University, 2022)
Background: Hepatocellular carcinoma (HCC) is the most common type of liver cancer and one of the most malignant neoplasms with high incidence and mortality in humans worldwide. The complex nature of the disease and its high resistance to systemic therapies result in poor prognosis for patients with advanced HCC.  Case Report: In March 2017, the patient was admitted to the Department of Oncological Surgery, where a non-anatomical tumor resection was performed. Three years later, the patient developed a single change in segment 8 of the liver that was a relapse of the neoplastic process. Based on the Bracelon Criteria, the patient was qualified for the 1st stage of chemoembolization using the Seldinger method. In the presented patient as a result of the applied treatment, the neoplastic process was stabilized.  Conclusion: The chemoembolization treatment that was applied to the presented patient turned out to be the correct treatment option. After only the first stage of chemoembolization, the patient regressed the neoplastic lesion.